Representation of Women’s Abortion Experiences in Jeritan Dalam Botol Short Stories By Intan Paramaditha: A Critical Discourse Analysis of Sara Mills' Perspective - Rakhmasari, Dwi Lia (English Education and Literature Journal (E-Jou), 2024)
Literary works have a big role in shaping and changing people's thoughts, feelings, attitudes, opinions, and behaviors about women. This is inseparable from the ideology of feminism of literary works, one of which is in the form of short stories (short stories) based on a gender perspective. This paper aims to describe Sara Mills feminist ideology using a procedure for simultaneous analysis of critical discourse. Based on this goal, the author encourages the author to study in a literature study entitled " Representation of Abortion Women in Short Stories Jeritan dalam Botol by Intan Paramaditha: A Critical Discourse Analysis of Sara Mills' Perspective". This type and approach of research is a qualitative-descriptive method with a method of critical discourse analysis developed by Sara Mills, which is also often referred to as critical discourse analysis with a 'feminist' perspective. The results of the writing show the perspective in which women are beings who have the right to their bodies absolutely because they are the ones who best understand and understand their own circumstances. The act of Abortion is also as a self-existence against patriarchy even though the act of abortion is considered by the wider community as an act of error, in this short story the author tries to narrate the acceptable reasons for the act of abortion both from the abortionist and those that help the abortion process (abortion shaman). The problem of abortion is not only death but a complexity in life choices.